If the answer is 1-2/3m what is the question>

How can you solve equations like these?

9r + 7 = 4r - 8

Need to get the r on one side.
1st- subtract 4r from the right side of the = sign. What you do to one side do to the other. 9r-4r+7=4r-4r-8. 5r+7=-8
2nd- subtract 7 from the left side to get r's by themselves. 5r+7-7=-8-7....5r=-15.
Divide 5r by 5.....remeber do it to both sides......5r/5=-15/5......r=-3
check answer.
9(-3)+7=4(-3)-8....-27+7=-12-8............-20=-20

Thanks for your help. I'm completely lost. Can you explain how 9r+7 = 4r-8?

pasheeta pasheeta answered
15 years ago

r=-3

Anonymous Anonymous answered
15 years ago

4.9u+5.87=23.81

Anonymous Anonymous answered
11 years ago

what is rule for input value of n?

Explain Bot Explain Bot answered
8 months ago

Certainly! The equation 9r + 7 = 4r - 8 is a linear equation with variable r. To solve it, we need to isolate the variable r on one side of the equation. Here's a step-by-step explanation of how to do that:

Step 1: Start by subtracting 4r from both sides of the equation to get rid of it on the right side. This is done to create a coefficient of 0 for 4r on the right side of the equation. By performing the subtraction, we have:

9r - 4r + 7 = 4r - 4r - 8

Simplifying this equation gives us:

5r + 7 = -8

Step 2: Next, subtract 7 from both sides of the equation to isolate the term with r on the left side. This is done to eliminate the constant term (+7) on the left side. By performing the subtraction, we have:

5r + 7 - 7 = -8 - 7

Simplifying this equation gives us:

5r = -15

Step 3: To solve for r, divide both sides of the equation by 5. This is done to isolate the variable r and obtain its value. By performing the division, we have:

5r/5 = -15/5

Simplifying this equation gives us:

r = -3

So, the solution to the equation 9r + 7 = 4r - 8 is r = -3.

Remember to always check the solution by substituting it back into the original equation to ensure that it satisfies the equation. In this case, substituting r = -3 into the original equation gives us:

9(-3) + 7 = 4(-3) - 8
-27 + 7 = -12 - 8
-20 = -20

Both sides of the equation are equal, confirming that the solution is correct.